Drug Abuse and the Nigerian Youth - Enamhe Dorn Cklaimz; Maxwell-Borjor Achuk Eba (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2020)
The incidence of drug abuse has become a problem that affects every country across the globe. The intake of substances affects both the physical and mental health of the users and the general public. Many people suffer from various health impairments such as hepatitis, heart attacks, respiratory infections, cancer, and neurological problems that lead to incapacitation and even death. The same thing applies to mental health issues like schizophrenia, anxiety, neuroses, psychoses, depression, and other mental illnesses. These problems have occurred due to the frequent intake of illicit drugs such as opioids and prescription over-the-counter drugs. The available literature reviewed shows the prevalence of drug abuse in the global sphere and Nigeria in particular. The study also shows how the problems become out of control as a result of either corruption among the security agents, drug trafficking and smuggling, or the amount of money involved in the business, which makes the drug barons devise many ways of accessing the drugs whenever the law enforcement agencies try to stop them. The present study investigates the effects of substance abuse on the health of users in Nigeria; the health consequences; the recent trend of substance abuse among youth; and the measures taken by the government to stop the menace. Both primary and secondary sources of data were utilised to collect data through textbooks, journals, internet sources, government and non-governmental agencies' reports, newspapers, and periodicals..